Rain attenuation time series synthesizer for satellite link in tropical/equatorial region - Al Amoodi, Tareq Omar (2012)
This paper presents and implements the Tropospheric attenuation time series synthesizer ITU-R P.1853 recommendation to simulate the time series rain attenuation of the propagation channel particularly in tropical/equatorial region. The accuracy and applicability of this recommendation will be validated by comparing long-term rain attenuation statistics produced with the currently available literature results. The primary objective of this paper is to investigate the performance of the rain attenuation time series synthesizer in terms of first and second order statistics (Rain Attenuation and Fade Duration). The 1st order statistic will produced by using to different values of rain rate for ITU-R 837 and the data of 3 years collected in Kuala Lumpur. Then comparison will be obtained for both ITU-R 1853 and ITU-R 618 to see the difference in 1st order statistic between them. Also, this thesis will show the effect of different elevation angles by using two different satellites (MEASAT 3A and TELSTAR 18). Moreover, the effect of different rain rate for two cities in Malaysia (Johor Bahru in the south, and Kedah in the north) will be investigated. On the other hand, 2nd order statistic fade duration will be observed in two ways. The first one is, to investigate the number of event of attenuation that occur during the rain for three different threshold attenuation points (4dB, 8dB and 12dB). The second one is, to investigate the probability of fade duration occurrence in Kuala Lumpur for two different satellites (MEASAT 3A and TELSTAR 18), and two threshold points (6dB and 10dB) for each satellite.